A unified method to extract the effective mobility in InGaAs metal-insulator-semiconductor field-effect-transistors using scattering-parameters. (December 2019) - Rho, Tae-Beom; Jo, Hyeon-Bhin; Kim, Tae-Woo; Kim, Dae-Hyun
Abstract: In this letter, we propose a unified method to extract the effective mobility ( μeff ) of In0.52 Al0.48 As/In0.7 Ga0.3 As/In0.52 Al0.48 As single-quantum-well (SQW) metal-insulator-semiconductor field-effect-transistors (MISFETs). The proposed method relies only on the measured high-frequency scattering-parameters (S-parameters) of the MISFETs in the linear regime. Two key metrics of MOS devices, intrinsic output conductance (go_i ) and intrinsic gate capacitance (Cg_i ), were extracted directly from the measured S-parameters using two-port network parameter theories, allowing us to compute the effective mobility of the MOS devices. Since the method only requires the small-signal S-parameter measurement data, it would be applicable to any kind of FETs and could be fruitful for studying the dependence of the effective mobility on lateral electric field intensity.